2021
DOI: 10.1177/1403494821990284
|View full text |Cite
|
Sign up to set email alerts
|

Public-health risks from tea drinking: Fluoride exposure

Abstract: Aims: Due to new evidence on fluoride neurotoxicity during early life, this study examined maternal exposure to fluoride through tea consumption in a low-fluoride region and measured fluoride releases from commercially available teas (tea bags and loose teas) to determine the need to limit fluoride exposure. Methods: Maternal urine fluoride (MUF) concentrations were measured in spot urine samples ( N=118) from first-trimester pregnant women and in prepared tea infusions made with deionised water from 33 brand … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 28 publications
3
11
0
Order By: Relevance
“…Participants who reported drinking green, black, or white tea had a 0.13 mg/L higher level of UF than those who did not drink tea, controlling for covariates . This finding is consistent with previous research demonstrating the large contribution of tea intake to urinary fluoride [17,47,[49][50][51] and bone fluoride levels [46]. Tea plants are capable of hyper-accumulating fluoride from the soil into their leaves, particularly if the tea is grown in acidic soil [47].…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Participants who reported drinking green, black, or white tea had a 0.13 mg/L higher level of UF than those who did not drink tea, controlling for covariates . This finding is consistent with previous research demonstrating the large contribution of tea intake to urinary fluoride [17,47,[49][50][51] and bone fluoride levels [46]. Tea plants are capable of hyper-accumulating fluoride from the soil into their leaves, particularly if the tea is grown in acidic soil [47].…”
Section: Discussionsupporting
confidence: 92%
“…Tea plants are capable of hyper-accumulating fluoride from the soil into their leaves, particularly if the tea is grown in acidic soil [47]. Pregnant women who are daily tea drinkers have significantly higher levels of urinary fluoride levels compared to those who rarely consume green, black, white, or oolong tea [51]. Till et al [17] found that black tea, but not green tea, accounted for approximately 5% of the variance in urinary fluoride levels measured in pregnant women.…”
Section: Discussionmentioning
confidence: 99%
“…We also consider a future review and meta-analysis on the green tea-induced injury to the liver, using the PRISMA criteria [40]. Krishnankutty et al bring the possibility of the toxic effect of the water used for teas [41]. Fluoride exposure increases with tea consumption, which has been linked to developmental neurotoxicity in pregnant women.…”
Section: Pathophysiology Of Hili Resulting Frommentioning
confidence: 99%
“…Fluoride exposure increases with tea consumption, which has been linked to developmental neurotoxicity in pregnant women. As the fluoride release from tea varies widely, the fluoride concentration should be indicated on tea packages to allow consumers to make informed decisions on minimizing their fluoride exposure [41]. Another group of researchers measured the fluoride content in infusions of commercially available black, green, and white teas [42].…”
Section: Pathophysiology Of Hili Resulting Frommentioning
confidence: 99%
“…The fluoride concentration in drinking water roughly equals the fluoride concentration in urine (National Research Council, 2006), as also recently shown in the Canadian cohort of pregnant women (Till et al., 2018). In addition to fluoridation, some types of tea, such as black tea, constitute an additional source of exposure (Krishnankutty et al., 2021; Rodríguez et al., 2020; Waugh, Godfrey, Limeback, & Potter, 2017).…”
Section: Introductionmentioning
confidence: 99%